Advancing sustainable development goal 8 Targets: The role of institutional Quality, economic Complexity, and state fragility in G20 nations (2000–2023) - Mohammad Naim Azimi; Mohammad Mafizur Rahman; Tek Maraseni (Research in Globalization)
As the global community nears critical milestones in achieving the Sustainable Development Goals (SDGs), the interplay of dynamic forces continues to reshape progress trajectories. This study explores the advancement of SDG 8 targets (“Decent Work and Economic Growth”) through the lens of three increasingly prominent factors: institutional quality, economic complexity, and state fragility, focusing on the G20 nations from 2000 to 2023. Guided by an extensive literature review, three research questions, and nine hypotheses, this study formulates four empirical models aligned with four SDG 8 targets and employs the cross-sectionally augmented autoregressive distributed lags model, further validated through dynamic common correlated effects mean group estimators. The findings reveal that economic complexity, institutional quality, and renewable energy significantly enhance economic growth and labour productivity, while reducing unemployment, and CO2 emissions. In stark contrast, state fragility and primary energy use exert detrimental impacts, underscoring the negative influence of macroeconomic instability and the persistent reliance of growth and labour productivity on primary energy sources, which intensify unemployment and CO2 emissions. Additionally, globalisation, human development, environmental technologies, urbanisation, and foreign direct investment continue to positively influence growth and labour productivity while mitigating unemployment and CO2 emissions. Under the combined influence of economic complexity, state fragility, and institutional quality, the findings validate the Environmental Kuznets Curve hypothesis, revealing a redefined turning point shaped by these metrics. Beyond this threshold, the environmental consequences of achieving SDG 8 targets are expected to abate, laying a critical foundation for the policy implications outlined in the study.